The Impact of Cyberattack Mitigation Strategies on Customer Satisfaction with Electronic Banking Services: An Applied Study on the Palestinian Banking Sector - Talahmeh, Ishaq A.H.; Dar Yasin, Mira; Abu Srhan, Eman; Ghouniam, Karmel; Jaber, Hadil (Ahliya Journal of Business Technology and MEAN Economies, 2024)
The study aimed to explore the impact of measures to address the risks of cyberattacks on customer satisfaction with electronic banking services through an applied study of the Palestinian banking sector. The study adopted a quantitative approach, selecting a sample of 346 users of electronic banking services. A questionnaire was used as the data collection tool, and the data were analyzed using SPSS software. The results indicated a statistically significant positive impact of measures to address cyberattack risks, along with technical, organizational, financial, and social dimensions, on customer satisfaction with electronic banking services. The study recommended enhancing cybersecurity systems, improving the technical user experience, developing organizational policies, and raising customer awareness about cyber risks and how to handle them. The originality of the study lies in its contribution to examining the impact of cybersecurity’s technical, organizational, financial, and social dimensions on customer experiences. It also provides practical recommendations to strengthen cybersecurity and enhance user satisfaction.